Peran Divisi Pemasyarakatan dalam Memberikan Pembinaan Terhadap Narapidana: Studi di Kantor Wilayah Kementerian Hukum dan Hak Asasi Manusia Sumatera Utara - Fajar sitorus; Janpatar Simamora (ALADALAH: Jurnal Politik, Sosial, Hukum dan Humaniora, 2025)
The correctional division has an important role in providing guidance to inmates or prisoners. This development of convicts is one of the main tasks of the correctional division at the ministry of law and human rights, which aims to prepare inmates so they can reintegrate into society well. This research serves to analyze the role of the correctional division in the development process, including rehabilitation, education and skills training. In the process of coaching prisoners, there will be many activities involved, for example worship, etc. which serve to change their lives for the better in the future after they are released. The internship shows that the correctional division has made serious efforts in providing coaching programs.